The contribution of the anthropometric measurements in selecting basketball players under 16 years old from trainers' perspective (a field study on the clubs of Khenchela and Batna middle schools) - Meddour, Houdhifa; Zemmouri, Belkacem (sports creativity, 2025)
This study aims to understand if the sport selection on the level of basketball clubs in school sports of Khenchela and Batna middle schools is occurring in a scientific basics; it also aims to understand the role of the body measurements in the process of selecting basketball players under 16 years old. The results of the study indicate that the sport selection process was done under a scientific basics; on the other hand, the study shows that both the coaches and the sport teachers did not apply all the anthropometric measurements of basketball during the process of selection on the level of the basketball clubs in school sports of middle school of Khenchela and Batna